Consumers activism: The Facebook boycott of cottage cheese - Igal Hendel; Saul Lach; Yossi Spiegel (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2015)
We study a consumer boycott on cottage cheese that was organized in Israel on Facebook in the summer of 2011 following a steep increase in prices after price controls were lifted in 2006. The boycott led to an immediate decline in prices which stayed low more than three years after the boycott. We find that (i) demand at the start of the boycott, at the new low prices, would have been 30% higher but for the boycott, (ii) own price elasticities and especially cross price elasticities increased substantially after the boycott, and (iii) post-boycott prices are substantially below the levels implied by the post-boycott elasticities of demand, suggesting that firms lowered prices due to fears of the boycott spreading to other products, of new price controls, and of possibly class action law suits.
Keywords: L1; D12; 330; consumer boycott; social media; price elasticities; Konsumentenboykott; Social Web; Wirkungsanalyse; Käse; Preis; Preiselastizität; Schätzung; Israel